Moon garden [videorecording (DVD)] - Harris, Ryan Stevens; Duke, Augie; Davis, Brionne; Ignis, Morgana; Harris, Haven Lee (Oscilloscope Laboratories, 2024)
A comatose five-year-old girl travels through a darkly surreal industrial wonderland, haunted by a nightmarish spectre that feeds off her tears. Through her fear, she must follow her mother's voice -- staticky and cutting out -- to find her way back to consciousness.